Digital effects in graffiti art and its applications in printed fabric designs (Al-Academy, 2025)
The current research aims to identify 1- Graffiti art. 2-Digital art and its impact on printed fabricsThe researcher adopted the descriptive-analytical approach and the experimental approach because it is the most appropriate with the directions of the current research, as the research population consists of (25) samples that were chosen intentionally, and the research sample was chosen intentionally from the total population, which numbered (3) design models, meaning a percentage of (8.3%). ) Due to similarity and repetition from the research community, a form for the analysis axes was prepared based on the indicators of the theoretical framework.The research came up with the most important results: Graffiti art works reflect one of the systems of mass communication in general and the art of textile design in particular, as in samples (1, 2, 3).The most important conclusions are: Nature played an important role in the emergence of colors that the designer used to express what was inside him to accomplish a wonderful design work. Graffiti artists seek to communicate their ideas and methods in an affirming way. In the end, it is not only a visual art, but rather a visual act in which writing is combined with the image.